1998
DOI: 10.7164/antibiotics.51.722
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of MC-02,331, a New Cephalosporin Exhibiting Potent Activity Against Methicillin-resistant Staphylococcus aureus.

Abstract: A systematic approach toward building activity against methicillin-resistant staphfocused on finding the optimal linkage between the cephem nucleus and a biphenyl pharmacophore, which established that a thio linkage afforded potent activity in vitro. Efforts to optimize this activity by altering substitution on the pharmacophore afforded iodophenylthio analog MC-02,002, which although highly potent against MRSA, was also highly bound to serum proteins. Further work to decrease serum protein binding showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Methicillin exhibited an even poorer binding affinity to PBP2a* than did benzylpenicillin, as indicated by a 36-fold decrease in the k 2 / K d value. This is consistent with the observation that the MIC value of methicillin against MRSA was about 32-fold higher than that of benzylpenicillin ( , ). If the individual parameters are compared for the two compounds, the decrease in the binding efficiency for methicillin is mostly due to the decrease in k 2 (∼22-fold), implying that the step of the ester bond formation plays a more important role than the first step of molecular recognition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Methicillin exhibited an even poorer binding affinity to PBP2a* than did benzylpenicillin, as indicated by a 36-fold decrease in the k 2 / K d value. This is consistent with the observation that the MIC value of methicillin against MRSA was about 32-fold higher than that of benzylpenicillin ( , ). If the individual parameters are compared for the two compounds, the decrease in the binding efficiency for methicillin is mostly due to the decrease in k 2 (∼22-fold), implying that the step of the ester bond formation plays a more important role than the first step of molecular recognition.…”
Section: Discussionsupporting
confidence: 92%
“…Compound 1 is a cephalosporin described early by R. Woodward and co-workers (31). It was recently demonstrated that the β-lactam (named MC02,002) and its derivatives exhibited high activities in binding membrane-anchored PBP2a and against gram positive bacteria including MRSA (6). Three or four new β-lactams with PBP2a-binding affinity comparable to that of Compound 1 have also been reported by scientists of several pharmaceutical companies (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This PBP is causally connected with methicillin resistance, as it functions as a transpeptidase and is not efficiently inhibited by commercially available ␤-lactams, in contrast to the other transpeptidases in staphylococci, PBP 1, PBP 2, and PBP 3. However, the poor affinity of PBP 2Ј for ␤-lactam antibiotics does not seem to be inherent in the ␤-lactam structure since new carbapenems and cephalosporins that are good inhibitors of PBP 2Ј have recently been described (1,6,11,12,14,20).Ro 63-9141, the active principle of the water-soluble prodrug Ro 65-5788, is a novel parenteral cephalosporin with broad-spectrum activity against gram-positive and gram-negative pathogens. It differs from older, broad-spectrum cephalosporins in that it has antibacterial activity against MRS isolates.…”
mentioning
confidence: 99%
“…These include the use of antibiotic combinations (8,36,49), the development of new members of existing antibiotic classes (5,15,16,24,27), and the introduction of novel agents (28,44). Novel classes will be particularly advantageous since such agents, with unique modes of action, are likely to circumvent existing resistance mechanisms (3).…”
mentioning
confidence: 99%